Monoclonal anti-endoglin antibody TRC105 (carotuximab) prevents hypercholesterolemia and hyperglycemia-induced endothelial dysfunction in human aortic endothelial cells - Tripska, Katarina; Igreja Sá, Ivone Cristina; Vasinova, Martina; Vicen, Matej; Havelek, Radim; Eissazadeh, Samira; Svobodova, Zuzana; Vitverova, Barbora; Theuer, Charles; Bernabeu, Carmelo; Nachtigal, Petr (Frontiers in Medicine, 2022)
Endoglin (Eng) is a co-receptor of the transforming growth factor β superfamily playing an important role in endothelial dysfunction. TRC105 (carotuximab) is a monoclonal antibody that blocks Eng and its downstream Smad signaling pathway. Here we have investigated for the first time the effects of TRC105 treatment on the development of endothelial dysfunction induced by 7-ketocholesterol (7K) or high glucose (HG), focusing on Eng expression, signaling, and function. In the hypercholesterolemia study, human aortic endothelial cells (HAECs) were treated with TRC105 (300 µg/mL) for 1 hour, followed by the addition of 7K (10 µg/mL) for another 12 h. In the hyperglycemia study, HAECs were exposed to HG (45 mM) for 60 hours, followed by the addition of TRC105 for another 12 hours, and cells treated with 5mM glucose and 40 mM mannitol served as control. Protein levels, adhesion, and transmigration of monocytes were assessed by flow cytometry, mRNA expression was measured by qRT-PCR. 7K and HG treatment increased protein levels of NF-κB and Eng and adhesion and transmigration of monocytes through HAECs monolayer. TRC105 pretreatment reduced the 7K- or HG-induced Eng protein levels and pSmad1/5 and pSmad2/3 signaling. Despite increased protein levels of P-selectin and VCAM-1, TRC105 mediated blockage of Eng prevented 7K- and HG-induced adhesion and transmigration of monocytes through endothelial monolayers. These results suggest that TRC105 mediated Eng blockage can counteract the hypercholesterolemia- and hyperglycemia-induced endothelial dysfunction in HAECs, suggesting that Eng might be a potential therapeutic target in disorders associated with elevated cholesterol and glucose levels.